2019
DOI: 10.1177/1934578x19852430
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Regulate Lipid Droplets Biogenesis in Drosophila melanogaster

Abstract: Lipid droplets (LDs), cytosolic fat storage organelles, are emerging as major regulators of lipid metabolism, trafficking, and signaling in various cells and tissues. LDs are altered in cardiovascular and neuronal disorders, inflammation, obesity, and cancer. Flavonoids comprise different classes of molecules, characterized by a well-known antioxidant activity and a beneficial effect in several diseases. However, the cellular mechanism by which different classes of flavonoids improve health is poorly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(82 reference statements)
1
8
0
1
Order By: Relevance
“…Nrf2 modulates the response to ER stress and autophagy and mediates the crosstalk between lipid metabolism and antioxidant defense ( Jiang et al, 2015 ). NAR, as other flavonoids, is involved in regulating metabolism homeostasis ( Fantin et al, 2019 ). Moreover, NAR binds to calcium channels with two-pore domains (TPC2) and to lysosomal wide conductance calcium channels (BKCa), altering the ionic homeostasis of lysosomes, increasing the concentration of Ca 2+ and H + ions ( Saponara et al, 2009 ; Pafumi et al, 2017 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Nrf2 modulates the response to ER stress and autophagy and mediates the crosstalk between lipid metabolism and antioxidant defense ( Jiang et al, 2015 ). NAR, as other flavonoids, is involved in regulating metabolism homeostasis ( Fantin et al, 2019 ). Moreover, NAR binds to calcium channels with two-pore domains (TPC2) and to lysosomal wide conductance calcium channels (BKCa), altering the ionic homeostasis of lysosomes, increasing the concentration of Ca 2+ and H + ions ( Saponara et al, 2009 ; Pafumi et al, 2017 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…To our knowledge, the activity of these enzymes has not been related to Hr96 until now. In the same line, Hr96 modulates the Minotaur ( mino ) activity, a conserved glycerol-3-phosphate O-acyltransferase responsible for triglycerides synthesis and lipid droplets biogenesis (Fantin et al, 2019 ). It has been shown that when this enzyme is down-regulated as observed upon bacterial infection, there is a progressive loss of lipid energy stores (Dionne et al, 2006 ), meanwhile, its expression is increased in the face of starvation (Fujikawa et al, 2009 ) possibly promoting a mitochondrial adaptation toward lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It interrupts the siphon membrane. It goes into the larval body through the siphon and devastates the siphon membrane by interfering with the phospholipidbinding so that the membrane ruptures (Fantin et al, 2019) . The breakage can obstruct absorption the oxygen.…”
Section: Discussionmentioning
confidence: 99%